Sentidos das interações entre tecnologia e sociedade na formação de engenheiros: limites e possibilidades para repensar a educação tecnológica - Jacinski, Edson (2012)
The objective of this study is to analyze how two undergraduate Engineering courses at the Federal Technology University at Paraná (UTFPR) are attending the socio-educational recommended by the Brazilian National Engineering Curricular Directives (Diretrizes Curriculares Nacionais de Engenharia – DCNs) (BRASIL, 2002b). Among other aspects, they established the need to construct a professional identity which is more synthesized with political, economic, cultural, and environmental challenges of the current Brazilian and international reality. Our investigative perspective was especially directed to better understand the senses constructed concerning relationships between technology and society within Brazilian Engineering courses. On the one hand is the need to look at what accompanies the heterogeneous, frontier-based, co-constructed character negotiated from the curricular review process. On the other hand is the relevance of facing the determinist tension and regional socio-technical challenges to configuring the new engineering profile. As such, we seek to articulate a conceptual-methodological framework based on the Socio-technical Analysis theoretical perspective in Social Technology Latin-American Studies, as well as Bakhtin‟s discursive Circle dialogue perspective. The corpus was constituted upon legal and institutional documents related to implementing the DCNs within the two Brazilian Engineering courses, as well as semi-structured interviews with professors and students from these courses. Results show two curricular configurations in which the relationships between technology and society are understood to be dimensioned on different emphases: the first course analyzed showed a significant determinist technology-based perspective, translated into a curricular disciplinary organization, in which the emphasis geared predominantly to technological formation in its strictest sense, given that the market and industrial sector appear as the principle social players of the future engineer‟s contribution; while the second course studied revealed a dialogical tension between formal education geared to discussing the social aspects of technology in various sectors of society and a disciplinary curricular organization which gives rise to considerable challenges to overcoming such determinist tension.